Signatures of Selection in the Genomes of Chinese Chestnut (Castanea mollissima Blume): The Roots of Nut Tree Domestication - LaBonte, Nicholas R.; Zhao, Peng; Woeste, Keith (Frontiers in Plant Science, 2018)
Chestnuts (Castanea) are major nut crops in East Asia and southern Europe, and are unique among temperate nut crops in that the harvested seeds are starchy rather than oily. Chestnut species have been cultivated for three millennia or more in China, so it is likely that artificial selection has affected the genome of orchard-grown chestnuts. The genetics of Chinese chestnut (Castanea mollissima Blume) domestication are also of interest to breeders of hybrid American chestnut, especially if the low-growing, branching habit of Chinese chestnut, an impediment to American chestnut restoration, is partly the result of artificial selection. We resequenced genomes of wild and orchard-derived Chinese chestnuts and identified selective sweeps based on pooled whole-genome SNP datasets. Sweeps identified from pooled data were validated in an independent sample of individual whole-genome sequences of orchard chestnuts. Several putative sweeps aligned to domestication-associated regions in other woody plants. Annotations of predicted genes in putative sweep regions could indicate their usefulness in chestnut improvement.